(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Danyluk S. Features of Internet technology, "Electronic Mail" in the process of professional competence of future philologists. The paper deals with the highlighting of the formation of future philologists’ professional competence in the aspect of the usage of such Internet technology as e-mail in the educational process. Attention is focused on the variants of usage of this Internet technology in the educational process. Aims of usage of e-mail in the educational process are defined in the article.